Genotypic and phenotypic analysis of an oculocutaneous albinism patient: a case report and review of the literature - Qian Ma; Weiwei Wang (Journal of Medical Case Reports)
Abstract Background Oculocutaneous albinism is a rare autosomal recessive disorder caused by congenital melanin deficiency, resulting in hypopigmentation of the eyes, hair, and skin. This study included a Chinese family with an oculocutaneous albinism pedigree, in which the proband presented with oculocutaneous albinismcombined with secondary angle closure, which has been rarely reported in previous literature. This article primarily focused on the clinical and genetic examination results of this patient and provided recommendations for ophthalmologist to treat patients with oculocutaneous albinism in clinical practice. Case presentation The proband in this case study is a 53-year-old Chinese male who showed depigmentation of the skin, hair, iris, and fundus, accompanied by photophobia, decreased vision, high intraocular pressure, nystagmus, macular fovea hypoplasia, and cataracts. Owing to the opacity and expansion of the lens, the volume ratio of lens to eyeball was increased, causing crowded anterior segment, bombed iris, and narrowed chamber angle and, ultimately, leading to secondary angle closure. Whole-exome sequencing suggested that the two patients in the pedigree harbored the compound heterozygous variants c.230G > A (p. Arg77Gln) and c.832G > A (p. Arg278*) in the TYR gene, while the healthy member carried the TYR c.230G > A (p. Arg77Gln) variant, which was consistent with the autosomal recessive inheritance pattern and further confirmed the diagnosis was oculocutaneous albinism. On the basis of the above results, the patient was diagnosed with oculocutaneous albinism, senile mature cataract, and secondary angle closure in the right eye and ocular hypertension in the left eye, as well as bilateral nystagmus. Then, the patient was prescribed carteolol eye drops to control intraocular pressure and underwent phacoemulsification and intraocular lens implantation surgery for the right eye. Postoperatively, the patient’s intraocular pressure was effectively controlled, and visual acuity improved. Conclusion We report a patient with oculocutaneous albinism combined with cataract and secondary angle closure, and whole-exome sequencing suggested that he harbored TYR gene variants. Comprehensive examinations were important for identifying the causes of angle closure and making proper treatment strategies. Genetic testing enabled precise diagnosis and genetic counseling.